2013
DOI: 10.1186/1471-2350-14-46
|View full text |Cite
|
Sign up to set email alerts
|

The associations between the polymorphisms in the CTLA-4gene and the risk of Graves’ disease in the Chinese population

Abstract: BackgroundThe associations between the polymorphisms in Cytotoxic T lymphocyte-associated molecule-4 (CTLA-4) gene and Graves’ disease (GD) have been extensively investigated in Chinese population. However, the results were inconsistent. The objective of this study is to investigate the associations between the polymorphisms in CTLA-4 gene and the risk of GD by meta-analysis.MethodsWe searched Pubmed database, Medline (Ovid) database, CNKI database and Wanfang database, covering all studies until August 11, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 26 publications
3
10
0
Order By: Relevance
“…We found that the T allele occurs with greater frequency in brucellosis patients than in controls, indicating it is a risk factor for this disease. This finding is in accordance with several studies, which have shown associations between this variation and risk of COPD , Graves disease , autoimmune type 1 diabetes , acute anterior uveitis and multi‐factorial autoimmune diseases . However, this association was not found for Behcet disease , RA , and systemic lupus erythematosus .…”
Section: Discussionsupporting
confidence: 92%
“…We found that the T allele occurs with greater frequency in brucellosis patients than in controls, indicating it is a risk factor for this disease. This finding is in accordance with several studies, which have shown associations between this variation and risk of COPD , Graves disease , autoimmune type 1 diabetes , acute anterior uveitis and multi‐factorial autoimmune diseases . However, this association was not found for Behcet disease , RA , and systemic lupus erythematosus .…”
Section: Discussionsupporting
confidence: 92%
“…Except for HLA , CTLA-4 and CD40 are apparently the most popular susceptibility genes in autoimmune diseases. Meta-analysis has confirmed correlations between the CD40 –1C/T(rs1883832), +49A/G(rs231775) and CT60(rs3087243) polymorphisms and the risk of GD [21, 22]. In this study, our results showed that CD40 –1C/T(rs1883832), +49A/G(rs231775) and CT60(rs3087243) polymorphisms were associated with GD risk, but no such correlations were observed in other commonly seen SNPs.…”
Section: Discussionsupporting
confidence: 54%
“…It is plausible that abnormal expression of these co-signaling molecules plays a key role in the pathogeneses of autoimmune diseases including GD (Wang et al, 2013a(Wang et al, , 2009. Single nucleotide polymorphisms (SNPs) in the CTLA4 and CD40 genes had been widely demonstrated to be associated with GD in different populations by linkage analysis (Tomer et al, 2003), candidate gene association studies (Yang et al, 2012), genome-wide association studies (GWAS) (Chu et al, 2011;Wang et al, 2013b) and meta-analysis (Du et al, 2013;Li et al, 2012). A recent GWAS in China detected more susceptibility genes for GD within the entire genome, but these accounted for only about 10% of heritability, when, in fact, genetic factors contribute about 70%-80% to the development of GD (Simmonds, 2013).…”
Section: Introductionmentioning
confidence: 99%